Global PRoMiSe (Perioperative Recommendations for Medication Safety): protocol for a mixed-methods study. Issue 6 (30th June 2020) - Nanji, Karen C; Merry, Alan Forbes; Shaikh, Sofia D; Pagel, Christina; Deng, Hao; Wahr, Joyce A; Gelb, Adrian W; Orser, Beverley A
Abstract : Introduction: Medication errors (MEs), which occur commonly in the perioperative period, have the potential to cause patient harm or death. Many published recommendations exist for preventing perioperative MEs; however, many of these recommendations conflict and are often not applicable to middle-income and low-income countries. The goal of this study is to develop and disseminate consensus-based recommendations for perioperative medication safety that are tailored to country income level. Methods and analysis: The primary site of this mixed-methods study is Massachusetts General Hospital/Harvard Medical School. Participants include a minimum of 108 international medication safety experts, 27 from each of the World Bank's four country income groups (high, upper-middle, lower-middle and low-income). Using the Delphi method, participants will rate the appropriateness of candidate medication safety recommendations by completing online surveys using RedCAP. We will use Condorcet ranking methods to prioritise the final recommendations for each country income group. We will execute a comprehensive dissemination strategy for the recommendations across each country income group. Finally, we will conduct semistructured interviews with our participants to evaluate the initial adoption and implementation of the recommendations in each country income group. Ethics and dissemination: This study was approved by the Human Research Committee/Institutional Review Board at Partners Healthcare (2019P003567). Findings will be published in peer-reviewed journals and presented at local and international conferences. Trial registration number: NCT04240301 .